Pelatihan Pencatatan Laporan Keuangan Sederhana Bersama Ibu-Ibu Binaan UMKM Chabi Craft - Sella, Wan Maina; Aulia, Winestya Nur; Sari, Wulan; Afif, Zayan Aswa Nur; S.T, Zealandisia Visabillah; Faiza, Nurlaili Adkhi Rizfa (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This training aims to improve the understanding and skills of mothers assisted by UMKM Chabi Craft in recording simple financial reports. The service method is carried out through a practical approach, combining theoretical training sessions with direct practice in financial recording. Apart from that, discussion and question-and-answer methods are also applied to ensure in-depth understanding. The results of this training show a significant increase in the ability of mothers assisted by UMKM Chabi Craft to record simple financial reports. They are able to group and record financial transactions in a more structured and accurate manner. Apart from that, they can also understand the importance of financial records in managing their business. This is reflected in increased fluency in understanding the financial reports produced and the ability to make better decisions based on financial data. This training proves that with a practical approach and appropriate assistance, mothers assisted by Chabi Craft MSMEs can develop important skills in managing their business finances.